(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
Today, traditional education is being replaced by modern digital education. Distance learning is being implemented in all universities around the world. The use of virtual laboratories in organizing laboratory classes in physics has led to a qualitative and faster mastery of science by students. Students will gain knowledge, skills and qualifications that can be used in their future professional activities. The use of virtual laboratories helps students to expand their understanding of the laws of nature, the essence of the content and physical worldview, and the formation of a physical imagination.